Tinjauan Fiqih Muamalah Terhadap Kerjasama Bagi Hasil Pengelolaan Lahan Perhutani Di Desa Kutorojo - Andi Sasmito; Siti Qomariyah; Izza Sasky Lutfiana (el hisbah: Journal of Islamic Economic Law, 2022)
Perhutani's land management collaboration is unique because it uses three forms of cooperation in practice. This study aims to: 1) Find and understand the reasons for the practice of profit-sharing cooperation between Perhutani and the community in Kutorojo village using three forms of cooperation, 2) Finding Muamalah fiqh views on the practice of profit-sharing cooperation between Perhutani and the community in Perhutani land management in Kutorojo Village. This research is a type of field research using a conceptual approach technique, the sources used as objects in this research are Perhutani as the land owner and the land management community who have worked together for 5 years for the results of the residents of Kutorojo Village, Kajen District, Pekalongan Regency. The data collection techniques used in this study is the triangulation method: Observation, Interview, and Documentation. The results of the analysis show that: 1) the cooperation for sharing the results of land management owned by Perhutani in Kutorojo Village uses three forms of cooperation because it sees the potential of land owned by Perhutani which is possible to be utilized and increase the results for the parties, as for the three forms of cooperation, namely: Cooperation for land maturation in The first 2 years, Cooperation in planting and caring for pine trees, and cooperation in planting trees under stands or on the sidelines of pine trees. 2) Based on the author's analysis of the three forms of cooperation, if analyzed in the perspective of Fiqh Muamalah, the cooperation is valid, because it has fulfilled the pillars and legal requirements.